2012
DOI: 10.1002/jcb.24134
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol chemosensitizes breast cancer cells to melphalan by cell cycle arrest

Abstract: Melphalan (MEL) is a chemotherapeutic agent used in breast cancer therapy; however, MEL's side effects limit its clinical applications. In the last 20 years, resveratrol (RSV), a polyphenol found in grape skins, has been proposed to reduce the risk of cancer development. The aim of this study was to investigate whether RSV would be able to enhance the antitumor effects of MEL in MCF-7 and MDA-MB-231 cells. RSV potentiated the cytotoxic effects of MEL in human breast cancer cells. This finding was related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 34 publications
3
59
0
Order By: Relevance
“…18 The treatment with resveratrol increased the levels of activated checkpoint kinase 2 expression (p-Chk2), which showed a decrease of cyclin A expression. 19 While the levels of cyclin dependent kinase 2 (CDK2) remained unchanged by treatments, its active form [Thr(160)-phosphorylated CDK2] was decreased by treatment with resveratrol. 19 The activity of CDK7, the kinase that phosphorylates CDK2 at Thr(160), was inhibited by resveratrol.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…18 The treatment with resveratrol increased the levels of activated checkpoint kinase 2 expression (p-Chk2), which showed a decrease of cyclin A expression. 19 While the levels of cyclin dependent kinase 2 (CDK2) remained unchanged by treatments, its active form [Thr(160)-phosphorylated CDK2] was decreased by treatment with resveratrol. 19 The activity of CDK7, the kinase that phosphorylates CDK2 at Thr(160), was inhibited by resveratrol.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…19 While the levels of cyclin dependent kinase 2 (CDK2) remained unchanged by treatments, its active form [Thr(160)-phosphorylated CDK2] was decreased by treatment with resveratrol. 19 The activity of CDK7, the kinase that phosphorylates CDK2 at Thr(160), was inhibited by resveratrol. 19 Although the efficacy on the apoptosis process has been documented, the bioefficacy is yet a matter of debate.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…MDA-MB-231, one of the breast cancer cell lines commonly used in cancer research, normally has poor prognosis [2]. It is reported that, the combination treatment of phenolic compounds from plant such as resveratrol together with melphalan could inhibit MDA-MB-231 cells more efficiently [3]. Hence, natural phenolics had a great potential to be the anti-cancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested that resveratrol can chemosensitize breast cancer cells to chemotherapeutics drugs [16]. Recently, Sprouse et al…”
mentioning
confidence: 98%